Fitossociologia em ambiente de borda de fragmento de floresta estacional semidecidual - Moreira, Laylla Nunes (2009)
The following work was perfomed in a fragment of a seasonal semidecidual forest in Floresta Nacional de Pacotuba, located in Cachoeiro de Itapemirim, Espírito Santo. In the whole, 39 parcels of fixed area were delimited being 27 (10 x 30 meters) located o